Pengalaman Perawat dalam Melaksanakan Model Penugasan Tim pada Masa Covid - 19 di Rumah Sakit - Miftahul Khoiriyah Siregar; Dudut Tanjung; Rika Endah Nurhidayah (Journal of Telenursing (JOTING), 2023)
This study aims to explore in depth the experiences of nurses in carrying out the team assignment model during the COVID-19 period at the hospital. The data collection method used qualitative research by conducting in-depth interviews with nurses at the hospital. The results of this study indicate that there are 4 themes obtained, namely as follows: 1) implementation of the team assignment model during the COVID-19 period, 2) psychological responses during implementing the team assignment model during the COVID-19 period, 3) obstacles to implementing the team assignment model during the COVID-19 period. COVID-19, 4) hope after implementing the team assignment model during the COVID-19 period. In conclusion, there were 4 themes that participants perceived related to the experience of nurses in carrying out the team assignment model during the COVID-19 period at the hospital. Keywords: COVID-19, Team Assignment Model, Nurses